Attitude of Prospective Teachers towards the Curriculum and Teaching Learning Process of Pre- Service Education Programs in Islamabad - Fozia Fatima, Sabir Ali (JCTE, 2023)
This paper examined the attitude of prospective teachers’ attitude towards the curriculum and teaching learning process of pre-service education programs in Islamabad. All the B.Ed and M.Ed students from both public and private universities were conveniently taken as sample. Total 300 students were taken as sample. A self-designed survey was elected in this study.